THE IMPACT OF FAMILY PROBLEMS AND DEPRESSION ON SUICIDE; AN EMPIRICAL ANALYSIS OF DISTRICT MARDAN - Usman Ali; Shakeel Hayat; Sana Bibi (International Journal of Contemporary Issues in Social Sciences, 2024)
Suicide is the act of taking one’s own life by killing himself/herself. In times physical and mental stress, individuals most of the times are unable to make the right decision. Wrong decision can be very harmful for individual’s life, career and development. There are many problems which can make an individual mentally or physically upset and challenged. Problems like family problems and depression can make an individual feel marginalized, socially excluded, and mentally upset which most of the times results in suicide attempt. This study tried to have an insight of the major determinants of suicide in district Mardan. The study is based on primary data collected from different areas of district Mardan. The sample size of the study is 180. The data is analyzed descriptively and empirically. The descriptive analysis shows that male population attempt more suicides as compared to female population, and age group of 16 to 40 is the most affected age group from suicide while lower and lower middle income classes attempt more suicides in district Mardan. Binary logistic model is used to analyze the data empirically and the results shows that the problems like family problems and depression are found to be the prominent determinants of suicides in district Mardan. The empirical results show that family problems are positively related with suicide with an impact rate of 0.390. The more an individual face family problems, more will be his/her chances of attempting suicide. The results also conclude that suicide and depression are positively related. Depression is the worst form of mental situation and individual can be in. the empirical results show that the value of the impact of depression on suicide is. All these results show that in district Mardan the suicide rate is increasing due to more problems and complexities of life and more family and mental/physical problems. This study suggest that families and society must be more cooperative and helping in times of mental problems, failures, and physical illness to reduce suicide rate in district Mardan.